ANALISIS PREDIKSI KERUSAKAN PERKERASAN LENTUR BERBASIS IRI (INTERNATIONAL ROUGHNESS INDEX) DENGAN METODE IRMS-V3, RONET - Sarah Maghfirah; Muhammad Ridwan Anas; Emma Patricia Bangun (Jurnal Syntax Transformation, 2023)
The condition of road pavement is going to decrease during its service life. To keep a pavement functioning, maintenance must be continuously performed. However, the maintenance that has been carried out so far has not been carried out optimally because the budgeting system is still carried out annually based on the results of a road condition survey. The preparation of the budget is carried out annually by BBPJN SUMUT as the relevant stake holder, based on the FWD value with a back calculation program. This causes funding to become unsustainable so that it affects unsustainable handling as well. There are several methods for calculating predictions of future damage values ​​including IRMS-V3 and RONET. Both have a basis for calculating the value of IRI as the main variable in predicting damage. The purpose of this study is to use both methods and compare them to predict IRI values, traffic growth values, and also the remaining planned life values ​​in order to obtain a funding/budget planning scheme and the right type of treatment. The type of data used is secondary data sourced from North Sumatra BBPJN. The analysis is carried out by calculating the IRI value, traffic volume, and the remaining planned life for the next 5 years. Based on the results of the analysis obtained, road damage will occur more quickly using the RONET method. Road maintenance funds resulting from the IRMS-V3 method are more economical. Then validated using statistical t test. The results show that there is no difference in the average predicted IRI value, but there is a difference in the average predicted RSL value for the two methods